An Improved Hybrid Encryption Algorithm for RGB Images - Liu, Suolan; Yue, Chen; Wang, Hongyuan (International Journal of Advanced Science and Technology, 2016)
This paper presents a computationally efficient encryption scheme for RGB images. Firstly, the original plain-image is decomposed to three component images of R, G and B. Secondly, an improved gravitation model is used for value transformation by setting different encryption keys on each component. Thirdly, the improved Arnold transform is applied for position permutation. Finally, we obtain the encrypted image by composing the three component cipher-images. Experimental results show that encrypted image achieved by our algorithm can effectively resist security attacks.